Studi Awal Pengungkapan Keberlanjutan Berbasis IFRS S1 dan Nilai Perusahaan: Peran Risiko ESG - Yuliantari Astasuci Nalurita; Fatah Mario Andaru; Khalilul Rahman; Tiara Rani Santoso; Cahyaning Dewi Handayani (SUSTAINABLE, 2026)
This study investigates the impact of IFRS S1–based sustainability disclosure on firm value and examines the role of ESG risk during the pre-implementation period in Indonesia. A quantitative research design is employed using cross-sectional data from 40 companies included in the SRI-KEHATI 45 Index in 2024. The data are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that, during the pre-implementation phase, sustainability disclosures based on IFRS S1 do not exert a significant positive effect on firm value. In contrast, ESG risk shows a partial and significant positive influence on firm value. Nevertheless, ESG risk does not function as a moderating variable in the relationship between IFRS S1–based sustainability disclosure and firm value. This study contributes to the existing literature by offering empirical insights into the effects of IFRS S1 pre-implementation and the role of ESG risk on firm value. Furthermore, the findings provide practical implications for regulators and practitioners, highlighting the need to strengthen implementation guidelines, enhance disclosure quality monitoring, and improve formal compliance with IFRS S1.